EFEKTIVITAS ANGGARAN PARTISIPATIF DALAM PEMBANGUNAN INFRASTRUKTUR DESA DI KABUPATEN MUSI RAWAS - Abdika Jaya; Ikit Ikit (LPPM UNIVERSITAS BINA INSAN, 2016)
The purpose of this study was to study the budgeting process with participatory mechanisms in village infrastructure development, the process of implementing village infrastructure development budgeting based on guidelines for development planning and the effectiveness of participatory budgets. This research is a qualitative research that describes using questionnaires, interviews and documentation techniques as a data collection tool. The results of this study indicate that the people of Musi Rawas Regency have sufficiently participated in the process of developing the budget, the process of preparing the development budget is in accordance with the guidelines for development planning and the participatory budget is quite effective. The implication of this study is that the local government of Musi Rawas Regency must continuously and simultaneously increase community participation in the development budgeting process, provide more workshop activities, supervision and education training for village government officials on participatory budgets in development planning to be more effective in achieving village infrastructure development goals.